Different Stages of White Matter Changes in the Original HDLS Family Revealed by Advanced MRI Techniques. Issue 5 (10th June 2013) - Sundal, Christina; Jönsson, Lars; Ljungberg, Maria; Zhong, Jianhui; Tian, Wei; Zhu, Tong; Linden, Thomas; Börjesson‐Hanson, Anne; Andersen, Oluf; Ekholm, Sven
ABSTRACT BACKGROUND The temporal evolution of white matter (WM) changes on MR examinations in hereditary diffuse leukoencephalopathy with spheroids (HDLS) is largely unknown. Our purpose was to investigate the evolution of these WM changes with diffusion weighted/tensor imaging (DWI/DTI) and MR Spectroscopy (MRS). METHODS A newly diagnosed patient with HDLS from the original Swedish family was followed prospectively with 5 MRI as well as DWI/DTI and MRS examinations during 16 months. RESULTS The DTI eigenvalues demonstrated changes that suggested early myelin and axonal disturbances in the normal appearing WM (NAWM). DWI/DTI showed a rim of decreased diffusion progressively expanding through the WM from the initial frontal periventricular zones, and indicated complete destruction of axons and myelin in the area behind the front. MRS findings were suggestive of axonal destruction in the NAWM. CONCLUSION We describe HDLS changes in three temporal stages of development corresponding to lesions outside, in the vicinity of, and behind a characteristic rim centrifugally progressing from the ventricular horns. The axonal disturbances indicated by MRS changes in the NAWM support a primary axonal degeneration, as proposed in the original HDLS report, rather than axonal degeneration secondary to demyelination. These findings could help in differential diagnosis of HDLS.